Dwa pojęcia wieczności i niektóre konsekwencje wynikające z tego rozróżnienia - Chlewicki, Maciej (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
Eternity could be considered as both timeless “now” as well as the totalityof infinite time. In Western thought those two notions (or two meanings) coexist fora long time, however their senses, origins and context of functioning are different. Distinctionbetween those two meanings leads us to better comprehension of the very co cept of the eternity, and also provides us an useful tools to solve some classical philosophicalproblems connected with this concept, for example: problems of the eternity of the mathematics truths, eternity of the God or of the world.